Employability development in business undergraduates: A qualitative inquiry of recruiter perceptions. Issue 2 (17th February 2020) - Nicholas, Jennifer M.; Handley, Meg H.
Abstract: Campus recruiters play a pivotal role identifying talent and socializing students into employment. In this exploratory study, 16 recruiters participated in semistructured interviews in the business college of a large state-affiliated research university. Their perceptions emphasize meaningful learning and growth factors in support of developing student potential in contemporary recruitment practices. Analysis and discussion offer implications of practical importance to higher education stakeholders.